2004
DOI: 10.1176/appi.ajp.161.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Age at Onset of Schizophrenia

Abstract: The results indicate a strong association between use of cannabis and earlier age at first psychotic episode in male schizophrenia patients. Additional studies examining this possibly causal relationship are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
122
5
17

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(154 citation statements)
references
References 32 publications
10
122
5
17
Order By: Relevance
“…An earlier onset of psychosis is associated with a more severe course, irrespective of the duration of the illness. 9 The age of criteria onset being significantly different for males and females in this study corresponds to previous findings that the peak ages of onset are 15 to 25 years for men and 25 to 35 years for women. 10 The results indicating a strong association between the use of cannabis and age at onset of psychosis in male schizophrenia patients match those of a study in Dutch male schizophrenia patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An earlier onset of psychosis is associated with a more severe course, irrespective of the duration of the illness. 9 The age of criteria onset being significantly different for males and females in this study corresponds to previous findings that the peak ages of onset are 15 to 25 years for men and 25 to 35 years for women. 10 The results indicating a strong association between the use of cannabis and age at onset of psychosis in male schizophrenia patients match those of a study in Dutch male schizophrenia patients.…”
Section: Discussionsupporting
confidence: 89%
“…10 The results indicating a strong association between the use of cannabis and age at onset of psychosis in male schizophrenia patients match those of a study in Dutch male schizophrenia patients. 9 Early deviant behaviour emerged as the most important factor in determining age of criteria onset in the present study, with the early deviant behaviour group having the oldest age of onset and the more severe group the youngest.…”
Section: Discussionmentioning
confidence: 50%
“…Clinical evidence has confirmed such links. Early-onset cannabis use increases the risk of developing schizophrenia (Arseneault et al, 2002;Fergusson et al, 2003;van Os et al, 2002) as well as a worsen course of the disorder (Green et al, 2004;Veen et al, 2004). Several epidemiological studies report that early regular use of cannabis increases the risk of initiation of the use of other illicit drugs (Agrawal et al, 2004;Fergusson and Horwood, 2000;Lynskey et al, 2003;Yamaguchi and Kandel, 1984), supporting the cannabis gateway hypothesis of cannabis as a steppingstone toward abuse of other drugs.…”
Section: Introductionmentioning
confidence: 94%
“…(Cantwell et al, 1999;Veen et al, 2004;Henquet et al, 2005;Mauri et al, 2006;Koskinen et al, 2010;Mazzoncini et al, 2010;Barrigón et al, 2010). Several studies on schizophrenia have reported that patients with SUD have worse premorbid social functioning (Sevy et al, 2010;Mazzoncini et al, 2010;Compton et al, 2011;Schimmelmann et al, 2011), more severe symptoms at onset (Gearon and Bellack, 2000;Dawe et al, 2011), lower compliance and worse treatment response, thus more inappropriate use of mental health services, (Lambert et al, 2005;de Haan et al, 2007;Schimmelmann et al, 2011) with higher mental health costs (Bartels et al, 1993).…”
Section: Introductionmentioning
confidence: 99%